Analysis of foot function in terms of different pharmacological treatments in a cohort of patients with rheumatoid arthritis: a longitudinal study. - Gámez-Guijarro, Maria; Reinoso-Cobo, Andrés; Pardo Rios, Manuel; Ortega-Ávila, Ana Belén; Ramos-Petersen, Laura; Gijón-Noguerón, Gabriel; Lópezosa-Reca, Eva (BMC, 2025)
This study examines the influence of pharmacological treatments on foot functionality in patients with rheumatoid arthritis over a five-year period. A longitudinal analysis categorized patients into different treatment groups, assessing their foot function using the Foot Function Index (FFI) at the start and end of the study. The groups are based on their pharmacological treatment. Pharmacological treatment groups were categorized into: I methotrexate (MTX), II MTX plus biological treatments (including all variables), III biological treatment alone, and IV a miscellaneous group comprising patients with diverse treatments, including patients for whom various drugs had failed or who had not achieved remission with pharmacological treatment. The study included 206 RA patients with an average age of 58.32 years and a disease evolution of 15.28 years. The analysis of the FFI in total and across its domains of pain, disability, and activity revealed significant differences only in the pain domain (p=0.011), with a trend toward worsening over time observed in the other domains. Notably, MTX treatment showed improvement in the pain domain (decreasing from 45.76 in 2018 to 40.43 in 2023). Findings suggest that while pharmacological treatments are essential in managing rheumatoid arthritis, their impact on foot function is limited, with MTX demonstrating the most significant benefit in terms of pain reduction
Keywords: Artritis reumatoide; Pies; Farmacología; Pharmalogical treatment; Foot function; Rheumatoid arthritis